BINA MANUSIA DAN BINA USAHADI DESA WANUREJO KABUPATEN MAGELANG - Ridho Bagus Darmawan (Jurnal Pallangga Praja (JPP), 2022)
This research aims to describe the form of Human development and Business development through BUMdeseka Nawa Karsa wanurejo Village, Borobudur district, Magelang Regency. BUMdes eka Nawa Karsa hasthree (3) types of businesses established in 2016 to help the economy of the community in wanurejo Village. Thisresearch is descriptive research and uses qualitative approach, namely by way of researchers jumping directlyinto the field to conduct observations, interviews and documentation. The focus of this research is communityempowerment using two (2) indicators, namely with Human development and Business development. dataanalysis techniques are data collection, data reduction, data presentation, and conclusion drawing. The resultsshowed that Bina Manusia and Bina Usaha have not been running well. Through the indicators of Humandevelopment through BUMdes eka Nawa Karsa has been running well but has not gone well such as trainingand seminars that are lacking and the selection of recruitment of workers is less to the perpetrators and thecommunity assisted by BUMdes eka Nawa Karsa. Meanwhile, if seen from Bina Usaha for bumdes capitalin the form of funds and infrastructure facilities are still lacking so it is still constrained while the certificationof BUMdes assisted Community products has not been facilitated by BUMdes and the village government.so that researchers provide advice to add training and seminars to bumdes management and community andcapital assistance to bumdes management and community should be distributed regularly.